Good-bye Marianne : the graphic novel - Watts, Irene N.; Shoemaker, Kathryn E. (Toronto : Tundra books ; Plattsburgh, N.Y. : Tundra Books of Northern New York, 2008)
Marianne Kohn, a Jewish girl living in Berlin in 1938, watches as the Nazi regime tears her family and community apart, until finally she is forced to leave her mother and her home and travel to safety in England.
"Based on Good-bye Marianne by Irene N. Watts, published by Tundra Books, 1998"--T.p. verso.
Multicultural Review
Resource Links
Multicultural Review, March 2009
Resource Links, February 2009
4.5
Keywords: Holocaust, Jewish (1939-1945) -- Germany -- Berlin -- Comic books, strips, etc. -- Juvenile fiction; Jews -- Germany -- Berlin -- Comic books, strips, etc. -- Juvenile fiction; Kristallnacht, 1938 -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Historical fiction; Holocaust, Jewish (1939-1945) -- Fiction; Jews -- Germany -- Berlin -- Fiction; Kristallnacht, 1938 -- Fiction; Comic books, strips, etc; Graphic novels; Historical fiction; Holocaust, 1939-1945 -- Comic books, strips, etc. -- Fiction; Jews -- Berlin (Germany) -- Comic books, strips, etc. -- Fiction; Kristallnacht, 1938 -- Comic books, strips, etc. -- Fiction; Berlin (Germany) -- Comic books, strips, etc. -- Juvenile fiction; Berlin (Germany) -- Fiction; Berlin (Germany) -- Comic books, strips, etc. -- Fiction; Graphic novels; Historical fiction